Effect of short basalt fibers on durability, mechanical properties, and thermal properties of polylactic acid composites. Issue 1 (February 2019) - Han, Lu; Ma, Fangwu; Chen, Shixian; Pu, Yongfeng
The effect of basalt fiber (BF) content on the properties of BF-reinforced polylactic acid (PLA) composites was investigated. Composites with 10, 20, 30, 40, 50, and 60 wt% BF were fabricated. The results revealed that (1) the mechanical properties improved with increasing BF content. The maximum tensile strength and modulus of the composites (i.e. 140 and 5050 MPa, respectively) occurred at a BF content of 50%. The maximum flexural strength, that is, 159.5 MPa was two times larger than that of the pure PLA and was obtained at a BF content of 40%. However, the mechanical properties deteriorated at BF contents >50%. (2) BF can stop storage modulus loss and are effective in improving the crystallinity, as revealed by dynamic mechanical analysis and differential scanning calorimetry measurements. The crystallinity improved from 34.6% to 54.6% with BF addition. (3) After the accelerated aging test, pure PLA was too weak for testing. However, high values of the tensile modulus (i.e. 60% that of the nonaged samples) were maintained by the BF-reinforced PLA. This resulted possibly from the high crystallinity of the PLA composites. Therefore, suitable amounts of BF as reinforcements can yield improvements in the performance of PLA composites.